Entrainment by axisymmetric jets impinging on a flat plate - Nobbs, K. W.; Searle, N. (College of Aeronautics, 1966)
An experimental technique is described for the determination of the entrainment in an axisymmetric gaseous jet impinging normally on a flat plate situated below the nozzle. Typical results are given of experimental work carried out using this technique for an Rix jet flowing into a like atmosphere of similar density. These results suggest that the relationships describing the entrainment are: (a) m/mo = 0.3 hid for the axial jet, and (b) mimo = 0.6 Rid for the wall jet. It is also deduced that the growth of the *wall jet is described by the equation: 5 w r approximately. Some experimental results are given for a jet at a higher temperature than the surrounding atmosphere.